Liquefaction Susceptibility Zonation in Lempuing Subdistrict, Bengkulu City, Indonesia - Mase, Lindung Zalbuin (Department of Civil Engineering, Diponegoro University, 2019)
Zonation of liquefaction potential is the important thing in understanding the liquefaction impact on an area. The liquefaction Severity Index (LSI) method can be applied to determine the liquefaction vulnerability level. This paper presents a study of liquefaction using LSI method to compose the liquefaction vulnerability map in a coastal area of Bengkulu City i.e., Lempuing Subdistrict. This study was conducted by analyzing CPT data in Lempuing Subdistrict to obtain the Factor of Safety and the probability of liquefaction. Peak Ground Acceleration (PGA) was assumed as 0.5g, which refers to SNI 03-1726-2012. Furthermore, the value of liquefaction probability and factor of safety obtained was analyzed to obtain LSI index and adjusted to the specific categories i.e., very low (0<LSI<15), low (15<LSI<35), moderate (35<LSI<65), high (65<LSI<85), and very high (85<LSI<100). Based on the analysis result, Lempuing Subdistrict was categorized as a very high to the very low susceptible area to liquefaction. The very high susceptible area was located on the eastern Lempuing Subdistrict bordering to the Gading Cempaka Subdistrict. The high susceptible area was located on the northern Lempuing Subdistrict bordering the Tanah Patah Subdistrict. Moderate to very low susceptible areas were located in the middle, west, and south of Lempuing Subdistrict.